Antibody response to Plasmodium vivax in the context of Epstein-Barr virus (EBV) co-infection: A 14-year follow-up study in the Amazon rainforest - Luiz F. F. Guimarães; Bárbara A. Rodrigues; Michelle H. F. Dias; Matheus G. Barcelos; Maria F. A. Nascimento; Sâmick L. Moreira-Nascimento; Sofia L. Afonso; Barbara G. S. Abreu; Jaap M. Middeldorp; Francis B. Ntumngia; John H. Adams; Camila Fabbri; et al. (PLoS ONE, 2025)
Background To develop an effective vaccine against Plasmodium vivax, the most widely dispersed human malaria parasite, it is critical to understand how coinfections with other pathogens could impact malaria-specific immune response. A recent conceptual study proposed that Epstein-Barr virus (EBV), a highly prevalent human herpesvirus that establishes lifelong persistent infection, may influence P. vivax antibody responses. Here, it was investigated whether EBV could impact the longevity of humoral immune response to P. vivax. Methodology/principal findings A 14-year follow-up study was carried out among long-term P. vivax-exposed Amazonian individuals (272, median age 35 years), and included 9 cross-sectional surveys at periods of high and low malaria transmission. The experimental approach focused on monitoring antibodies to the major blood-stage P. vivax vaccine candidate, the Duffy binding protein region II (DBPII-Sal1), including a novel engineered DBPII-based vaccine targeting conserved epitopes (DEKnull-2). In parallel, the status of EBV infection was determined over time by the detection of circulating EBV DNA (EBV-DNAemia) and EBV-specific antibodies to lytic (VCAp18) or latent (EBNA1) antigens. Regardless of the malaria transmission period, the results demonstrated that one or multiple episodes of EBV-DNAemia did not influence the longevity of DBPII immune responses to both strain-specific (Sal-1) or strain-transcending (DEKnull-2) antibodies. Also, the average time in which DBPII-responders lost their antibodies was unrelated to the EBV serostatus. Considering all malaria cases detected during the study, there was a predominance of P. vivax mono-infection (76%), with a positive correlation between malaria infection and EBV-DNAemia. Conclusions/significance In an immunocompetent P. vivax-exposed adult population neither sporadic episodes of EBV-DNAemia nor antibody responses to lytic/latent EBV antigens influence the longevity of both strain-specific and strain-transcending DBPII immune responses. Further studies should investigate the role of acute P. vivax infection in the activation of EBV replication cycle.